Securing Data Transmission in Cloud using Encryption Algorithms - Nigam, Anjali; Singh, Vineet (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing provides an overwhelmingly versatile and flexible processing to associations that is accessible on interest. It lets enterprises to be fast, adaptable and ready to react quickly to the dynamic business situations. As cloud computing offers many advantages, it also has numerous security issues. The quantity of information exchanged over cloud is quite unsafe. The encryption specifications such as AES (Advanced Encryption Scheme), DES (Data Encryption Scheme), and 3DES (Triple Data Encryption Scheme) are widely used to solve such issues. But with the advancement in tools, these algorithms do not seem to be speedy and secure enough. In this paper we propose an encryption technique using two symmetric cryptography algorithms which supplies security to both the original file and the secret pass-code. The message to be sent is encrypted and decrypted using the AES algorithm. 3DES is used for encrypting and decrypting the secret key which encrypts the actual data to be transmitted.